ANALISA CUSTOMER EXPERIENCE SOTO KUDUS KEMBANG JOYO DENGAN METODE CUSTOMER SATISFACTION INDEX (CSI) DAN IMPORTANCE PERFOMANCE ANALYSIS (IPA) DALAM MENINGKATKAN KEPUASAN KONSUMEN - Dewanta Facrureza; Gabrian Marcel Wong (Bajang Institute, 2024)
This research was conducted to test hypotheses through a study of Soto Kudus Kembang Joyo on Sabang Street to understand customer experience with dimensions of accessibility, competence, customer recognition, helpfulness, personalization, problem-solving, promise fulfillment, and value for money at Soto Kudus Kembang Joyo on Sabang Street, which is used to enhance consumer satisfaction by taking 100 samples. The data collection used in this study is a quantitative method using questionnaires to Soto Kudus Kembang Joyo consumers as primary data. The research results indicate that consumer satisfaction is satisfied with the services and products provided with an average Customer Satisfaction Index data that almost reaches 80%. The conclusion of this research is that the customer experience at Soto Kudus Kembang Joyo is considered satisfactory, and the owner is expected to pay attention to some weakening attributes and maintain quality.